Customer Retention and Related Factors Analysis in Financial Services Company - Heru Santosa Hadiyanto (Binus Business Review, 2021)
High competition requires companies to maintain their consumers, so they do not turn to competitors. Besidesthat, the high acquisition cost to get new customer makes many companies shift their focus to customer retention.It also happens in the financial services industry in Indonesia. Their product is relatively homogeneous with tightregulations, price war from competitors, and the high credit risk to acquire new customers. It makes financecompanies concentrate on consumer retention. The research aimed to identify the factors that most influenceconsumer retention in the financial services company. Cluster random sampling technique was applied to getthe sample of the population. Secondary data from one branch of a finance company in a particular geographicalcluster (2.858 customers) were used. The selection of branches or geographical clusters was selected randomly.Data analysis was conducted based on several determinant factors that affected consumer retention, such as theamount of loan to value, days past due that consumers had, monthly income, and the mileage from the customerdomicile to the company offices. Pearson correlation analysis was used to analyze these determinant factors.Based on several factors, mileage and loan to value have a highly significant relationship with customer retention.Meanwhile, the other variables do not have a significant effect on customer retention.